A Note on Limit Shapes of Minimal Difference Partitions - Comtet, A.; Majumdar, S.N.; Sabhapandit, S. (Журнал математической физики, анализа, геометрии, 2008)
We provide a variational derivation of the limit shape of minimal difference partitions and discuss the link with exclusion statistics